Multiple copulations in natural populations of lizards: evidence for the fertility assurance hypothesis - Uller, T; Olsson, M (2005)
Females of many species mate multiply to obtain material or genetic benefits. However, because of problems associated with estimating number of copulations, our understanding of female mating patterns in natural populations is very limited. We studied correlates of multiple mating over three years in populations of the viviparous common lizard, Lacerta vivipara, a species in which the number of copulations can be reliably inferred from the number of mating scars. Our results show that females with a high number of copulations had lower clutch size, but heavier offspring (controlled for a potential relationship between the two), than females with fewer copulations. This pattern could be driven by sexual selection, ecological, and environmental factors. More promiscuous females had lower proportion of infertile eggs, controlling for clutch size. Thus, one of the primary reasons for multiple copulations in natural populations of L. vivipara could be sperm limitation, or to avoid infertile males. © Koninklijke Brill NV, 2005.